Building capacity for HIV and implementation science among students in the United States: the stimulating training and access to HIV research experiences (STAR) program - Nwaozuru, Ucheoma; Tucker, Joseph D.; Thurston, Idia B.; Airhihenbuwa, Collins O.; BeLue, Rhonda; Tang, Weiming; Obiezu-Umeh, Chisom; Anikamadu, Onyekachukwu; Ameen, Khadijah; Herrara, Christian; Engelhart, Alexis; Patrick, Tochukwu; et al. (Frontiers in Public Health, 2025)
BackgroundExpanding HIV research capacity among the global majority (individuals identifying as Black/African American, American Indian and Alaska Native, Asian, Native Hawaiian and Other Pacific Islander, Multiracial, and Hispanic/Latino) is important. However, achieving national goals to increase the pool of implementation science and HIV early-stage investigators from underrepresented backgrounds remains elusive, largely due to limited investment in training and mentoring these individuals. To address this issue, we launched the Stimulating Training and Access to HIV Research Experiences (STAR) program, a partnership led by Saint Louis University and the University of North Carolina at Chapel Hill in collaboration with Georgia State University and Texas A&M University. The STAR program aims to establish a pathway for Underrepresented minority (UREM) students to engage in HIV and implementation science research.MethodsWe launched a crowdsourcing open call from November 30, 2022, to January 22, 2023, to identify potential trainees at the four participating institutions (Prompt: “How might we promote HIV prevention among youth aged 13–24 years in your community?”). The finalists from the crowdsourcing call participated in a 2-day designathon, which included didactic introductory lectures on HIV, dissemination and implementation science. The finalists participated in a 6-week innovation bootcamp, including modules on HIV research, implementation science, research ethics, and fieldwork experience with community partners. We assessed the acceptability of the STAR program through participant self-reported surveys on their experience and evaluation of the lectures.FindingsTwenty-four individuals applied to the STAR program by completing the crowdsourcing open call, 12 were selected for the designathon, and 10 completed the fellowship. The first cohort of STAR trainees (10 students—6 undergraduate and 4 graduate students) successfully completed the STAR innovation bootcamp. The innovation bootcamp culminated in seven proposals that the trainees implemented and evaluated over 12 months, with support from the research team, mentors, and participatory learning community. The implementation strategies proposed by the trainees include the use of peer engagement, storytelling, digital engagement tools, and artificial intelligence to promote awareness of HIV and increase the uptake of HIV testing. All the participants were satisfied with the STAR program (90% very satisfied and 10% satisfied) and indicated enthusiasm for pursuing academic and research careers in HIV and/or implementation science.ConclusionBuilding a pathway for UREM investigators is crucial to ending the HIV epidemic. The STAR program may enhance interest, build research capacity, and increase the UREM talent pool retained in this field.